A new electromembrane extraction probe for on-line connection with capillary electrophoresis for determination of substances in biological matrices - Opekar, František; Tůma, Petr (Talanta, 2023)
A miniature probe for electromembrane extraction is developed and constructed. The tubular probe with an internal volume of 1.1 μL is made of polypropylene hollow fiber with a supported liquid membrane of 85% nitrophenyloctyl ether (NPOE) with 15% bis(2-ethylhexyl)phosphonic acid (DEHP). The probe is connected on-line to the electrophoresis with short separation capillary via an air assisted flow gating interface cast from poly (dimethylsiloxane). The compact instrument is computer controlled via LabView. The probe parameters are tested for extraction of creatinine and basic amino acids from artificial solution and human urine. The sensitivity of the electrophoretic determination after 300 s extraction at 150 V compared to the sensitivity without extraction is 4.9-fold and 2.6-fold higher for creatinine and arginine, respectively. The RSDs for peak area measured from 5 repeated extractions of 50 μM solutions are 7.5%, 7.2%, 8.6% and 9.2% for Crea, Lys, Arg and His, respectively. The probe can be used for all-day measurements. The preparation of the probe is simple and requires no special tool.
Keywords: membrány umělé; Ethers; lidé; Membranes, Artificial; kreatinin; elektroforéza kapilární; Electrophoresis, Capillary; ethery; Humans; Creatinine